The era of the Crusades - Harl, Kenneth W.; Teaching Company (Chantilly, VA : Teaching Co., 2003)
History of the Crusades, from its origins to the final Muslim victory over the Crusaders in 1291.
lecture 1. The heirs of Rome -- lecture 2. Byzantine orthodox civilization -- lecture 3. Byzantine zenith in the Macedonian age -- lecture 4. The Failure of the heirs of Basil II -- lecture 5. Abbasid Baghdad and Fatimid Egypt -- lecture 6. The coming of the Seljuk Turks -- lecture 7. The recovery of Western Europe -- lecture 8. Kings and princes of Western Europe -- lecture 9. Warfare in Western Europe -- lecture 10. The papacy and religious reform -- lecture 11. Piety and pilgrimage -- lecture 12. Christian offensives in Spain and Sicily -- lecture 13. Alexius I and first crusade --lecture 14. From Clermont to Jerusalem -- lecture 15. Conquest and defense of Outremer -- lecture 16. Frankish settlement of Outremer -- lecture 17. Comnenian emperors and Crusader princes -- lecture 18. The Second crusade -- lecture 19. The Empire at bay -- lecture 20. The rise of Saladin -- lecture 21. Byzantine recovery under the Comnenians -- lecture 22. A renaissance of Byzantine letters and arts -- lecture 23. Trade and currency in the Mediterranean -- lecture 24. Cultural exchange in Gothic Europe -- lecture 25. The Horns of Hattin -- lecture 26. The Third crusade -- lecture 27. From Jerusalem to Constantinople -- lecture 28. The sack of Constantinople -- lecture 29. The world of Frankish Greece -- lecture 30. Splinter empires and orthodox princes -- lecture 31. Ayyubid Egypt and Seljuk Anatolia -- lecture 32. Crusader Cyprus and the Levant -- lecture 33. Venice and Genoa -- lecture 34. The Mongols and the legend of Pester John -- lecture 35. The royal crusaders -- lecture 36. The passing of the crusades.
Title from disc.
Thirty-six lectures on 6 discs in 3 containers.
Lectures delivered by Professor Kenneth W. Harl, Tulane University.
DVD, region 1.
Keywords: Crusades -- History; Middle Ages